Podnikatelský záměr - Čech, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Tato práce se zabývá zpracováním podnikatelského záměru v oblasti poskytování služeb. V práci se věnuji analýze trhu a současného stavu firmy a poté návrhem na její rozšíření.

This work puts mind to process of business plan in section of delivering services. I hold forth on analysis of a market and analysis current status of company in this work and then I devote to project on upgrading the company.
Business Plan
Keywords: Podnikatelský záměr; analýza trhu; návrh na rozšíření firmy; Business plan; analysis of market; project on upgrading the company